2017
DOI: 10.1111/jvh.12840
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of hepatitis B virus reactivation and subsequent hepatitis in patients with chronic hepatitis C receiving direct‐acting antiviral therapy

Abstract: To determine the clinical characteristics of hepatitis B virus (HBV) reactivation in patients undergoing interferon-free antihepatitis C virus (HCV) therapy, we examined HBV DNA in 25 HBV co-infected patients and 765 patients with resolved HBV infection during and after treatment with direct-acting antiviral agents (DAAs). Among those with HCV genotype 1, asunaprevir plus daclatasvir was administered to 160 patients, sofosbuvir (SOF) plus ledipasvir to 438 patients and paritaprevir plus ombitasvir and ritonavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…112 Earlier studies suggested that the risk is modest in individuals with OBI receiving tumor necrosis factor inhibitors, but recent studies found that the risk of HBV reactivation is very low in patients receiving these therapies. 103 Similarly, the risk of HBV reactivation is very low in individuals with OBI receiving direct-acting antiviral therapy for hepatitis C. [113][114][115] Given the shared transmission routes for HIV and HBV, and the immune impairment produced by HIV, OBI and HBV reactivations were more frequently reported in patients with acquired immunodeficiency syndrome. Following the widespread use of potent antiretroviral therapies, including antiretroviral agents with anti-HBV activity, reactivation of OBI has become negligible in the HIV population receiving appropriate therapy.…”
Section: Hbv Reactivationmentioning
confidence: 99%
“…112 Earlier studies suggested that the risk is modest in individuals with OBI receiving tumor necrosis factor inhibitors, but recent studies found that the risk of HBV reactivation is very low in patients receiving these therapies. 103 Similarly, the risk of HBV reactivation is very low in individuals with OBI receiving direct-acting antiviral therapy for hepatitis C. [113][114][115] Given the shared transmission routes for HIV and HBV, and the immune impairment produced by HIV, OBI and HBV reactivations were more frequently reported in patients with acquired immunodeficiency syndrome. Following the widespread use of potent antiretroviral therapies, including antiretroviral agents with anti-HBV activity, reactivation of OBI has become negligible in the HIV population receiving appropriate therapy.…”
Section: Hbv Reactivationmentioning
confidence: 99%
“…A total of 425 patients positive for HBsAg (including the 37 patients from the Egyptian study), and 1900 patients negative for HBsAg but positive for anti‐HBc were used to estimate the pooled risks. Nine studies (10 articles) were from East Asia, 6 from Europe, 1 from USA and 1 from New Zealand . All of these studies included patients on IFN‐free DAAs regimens for 8‐24 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…All of these studies included patients on IFN‐free DAAs regimens for 8‐24 weeks. While most of studies reported HCV genotype, only 3 studies reported HBV genotype . Risk of bias in these studies is summarized in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Severe outcomes have also been the subject of case reports. However, Gane et al 12 noted that 7 of 8 patients had an increase in HBV DNA during DAA therapy, but none had an associated hepatitis, and Tamori et al 13 found that only 3 of 22 (12%) had an increase in HBV DNA, all subclinical. Collectively, these data highlight the importance of definitions, something that has plagued the HBV reactivation literature in the setting of immunosuppression.…”
Section: Hepatitis B Reactivation With Hepatitis C Treatment: Bringinmentioning
confidence: 99%